Purpose and tasks of competition legislation of Ukraine: methodological approaches of determination - Корчак, Наталія Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
Purpose and tasks of competition legislation of Ukraine: methodological approaches of determination In the article are analysed offered in legal and economic literature of determination of protective aims of competition legislation on the whole and a purpose is formulated and the tasks of competition legislation of Ukraine are specified.